Analysis of Wollongong City Council using 7s’s of Galliers and Sutherland Methods - Gamayanto, Indra (Bina Nusantara University, 2017)
The research analyzed website of Wollongong City Council (WCC) and all the plans done by the WCC. It also showed details an Information Systems (IS) strategic plan for WCC. Although the WCC already had an integrated system, there were several key issues. The framework used to devise IS plan was seven stages (7S) of Gallier and Sutherland (G&S). The approach assisted WCC in locating the current stage of its Information Technology (IT) maturity. From the analysis undertaken, it finds that IT currently is within stages 4 and stage 5 in seven stages. The final result will be the framework of the design as recommendations to the WCC.